PERAN PENDIDIKAN ANAK DI GEREJA BAGI PEMBENTUKAN CALON PEMIMPIN BERINTEGRITAS - Suriyanti, Intan; Gulo, Fitriyani (JURNAL IMPARTA, 2024)
Children are the next generation of a nation, in the sense that the older group will later be replaced by the younger group who will continue everything in this life. They have a strategic role in the continuation of life. On a smaller scale, namely for the church, children are also the beginning of future generations who will carry on the sacred message, and will have an important role in the development of the church and state in the future. The better the teaching given to children from an early age, the better the future development of the church will be in order to create future leaders who are good, ethical and have high integrity. This research will discuss the role of children's education in the church in the formation of future leaders with integrity. The research was conducted qualitatively, through literature studies and also biblical research with analysis of the Bible related to education and church services in the field of children. Children's ministry, especially in spiritual teaching services according to God's Word, is very important because it is one of the responsibilities of the church. However, the church has challenges in providing education, namely challenges in the form of cultural context and secular environment, limited resources, technology, participation and also parental commitment. Facing these challenges, the church needs to develop creative, relevant and inclusive educational strategies and programs to meet the needs of children in their spiritual growth. It involves close collaboration between church leaders, staff, volunteers, and the church community as a whole. The church must provide repeated teaching in the form of teaching moral values, building character, cultivating exemplary leadership and developing spiritual awareness. Through strong and consistent spiritual education, children can grow into leaders with integrity, ready to lead with justice, honesty and love, and become inspiring role models for others.